(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Subacute sclerosing panencephalitis is a progressive neurological disorder of childhood and early adolescence. It is caused by persistent defective measles virus1.We report a ten years old normally developed female patient who came with a history of drop attacks while walking, declining scholastic performance, progressively increasing myoclonic jerks. She had history of measles at five years of age though she was vaccinated as per EPI schedule. Physical examination and cerebrospinal fluid findings along with EEG changes in addition supported its diagnosis as a case of SSPE. The presence of increased urinary excretion of copper in SSPE is so far not yet reported in any published literature. Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 113-115